Investigation on water adsorption on 3-crosslinked circular polyacrylamide membrane using ab initio, molecular dynamics and Monte Carlo calculations for dewatering microalgae - Villagracia, Al Rey C. (Animo Repository, 2019)
Microalgae has been identified as a source of biomass and biofuel which can be cultivated easily in large amounts given a small land area requirement. However, minimizing microalgae's moisture content to 10% has been a bottleneck due to its energy intensive requirement and/or poor-quality outcome. A solution for this is the low-energy efficient forward osmosis system which needs a water superabsorbent polyacrylamide (PAM) hydrogels to maintain the salt concentration on the draw solution. Water sorption on 3-crosslinked circular polyacrylamide membrane was investigated using ab initio principles, molecular dynamics and monte carlo calculations. The PAM structure was geometrically optimized using density functional theory, and then equilibrated at room temperature and 1 atm pressure for 1 ns using molecular dynamics simulation. Monte Carlo simulations at room temperature with 2,500,000 steps and geometry optimization per step were performed to identify the adsorption sites for 25, 50, 75, 100, 125, and 150 water molecules by calculating their adsorption energies under the Dreiding Forcefield Model. A mathematical model was fitted to identify the relationship of adsorption energies with the number of water molecules that can be absorbed. Results showed this material can potentially adsorbed 1082 kg - 2345 kg of water per cubic meter of material when translated from calculated amount of water molecules that was adsorbed per unit cell volume. This study serves as a foundation for exploration of the new material circular polyacrylamide membrane that can facilitate microalgae drying to produce biomass and biofuel. © Published under licence by IOP Publishing Ltd.